2015
DOI: 10.1038/jid.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Genetic Basis of Rosacea by Genome-Wide Association Study

Abstract: Rosacea is a common, chronic skin disease that is currently incurable. Although environmental factors influence rosacea, the genetic basis of rosacea is not established. In this genome-wide association study, a discovery group of 22,952 individuals (2,618 rosacea cases and 20,334 controls) was analyzed, leading to identification of two significant single-nucleotide polymorphisms (SNPs) associated with rosacea, one of which replicated in a new group of 29,481 individuals (3,205 rosacea cases and 26,262 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 27 publications
7
111
1
10
Order By: Relevance
“…Namely, our finding that HLA-B*4001 and HLA-DRB1*1302 were protective against glioma was consistent with prior observations that HLA-B*40 and HLA-DRB1*13 were enriched among the control group[17,18,21], although the association was not significant in those prior studies and the opposite direction of effect was observed in another study[22]. Although a previous GWAS found that rosacea (recently linked to glioma risk in a large Danish cohort[5]) is associated with three HLA alleles found to be in high linkage disequilibrium in our study (DRB1*0301, DQA1*0501, and DQB1*0201)[8], we did not observe these alleles to be associated with glioma risk, suggesting that the glioma-rosacea link is not likely due to shared HLA risk variants with pleiotropic effects.…”
Section: Discussioncontrasting
confidence: 75%
“…Namely, our finding that HLA-B*4001 and HLA-DRB1*1302 were protective against glioma was consistent with prior observations that HLA-B*40 and HLA-DRB1*13 were enriched among the control group[17,18,21], although the association was not significant in those prior studies and the opposite direction of effect was observed in another study[22]. Although a previous GWAS found that rosacea (recently linked to glioma risk in a large Danish cohort[5]) is associated with three HLA alleles found to be in high linkage disequilibrium in our study (DRB1*0301, DQA1*0501, and DQB1*0201)[8], we did not observe these alleles to be associated with glioma risk, suggesting that the glioma-rosacea link is not likely due to shared HLA risk variants with pleiotropic effects.…”
Section: Discussioncontrasting
confidence: 75%
“…Although little evidence is available on the genetic basis of rosacea, a recent genome-wide association study found that variants in three major histocompatibility complex (MHC) class II protein-coding genes ( HLA-DRB1*03:01 , HLA-DQB1*02:01 and HLA-DQA1*05:01 ) were associated with rosacea. 21 Recent fine mapping of MHC regions in IBD also suggested a primary role for HLA-DBR1*03:01 . 22 In addition to genetic predisposition, UV radiation and lifestyle factors may be associated with rosacea, which requires large prospective studies to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that Fusobacterium varium , which inhabits the enteral mucosa, was highly detected in colon tissue samples from patients with active ulcerative colitis (UC), along with increasing serum antibody levels of F. varium , a link between UC and Fusobacterium remains plausible [23]. The association between rosacea and UC has been well established by previous studies, based on the increased prevalence of UC in rosacea patients and the shared genetic background between rosacea and inflammatory bowel disease [10, 24]. In this regard, Fusobacterium may account for blood dysbiosis as well as enteral inflammation accompanied with rosacea, and thus may be a link between rosacea and UC.…”
mentioning
confidence: 99%